Effects of Floral Characters on the Pollination Biology and Breeding System of Iris setosa (Iridaceae): A Cold-Tolerant Ornamental Species from Jilin Province - Xiyue Zhang; Ruoqi Liu; Lifei Chen; Tianhao Pei; Yu Gao; Xi Lu; Yunwei Zhou (Biology)
Floral phenology and features are intricately linked to pollinator behavior and pollination systems. Iris setosa is one of the ornamental irises of the family Iridaceae with beautiful flowers and leaves, and little research has been reported on its pollination biology. This study analyzed how phenology, floral features, breeding systems, and pollinator visits affect reproductive success of I. setosa populations in Jilin Province. Field observations and pollination studies demonstrated that I. setosa reached the bud stage in late May, with an average flowering time of 30 days. The anthers were outwardly dehiscent toward the outer edge of the style branches. In herkogamy, the relative locations of the anthers and stigma remained unchanged during flower opening. The stamens matured first. The pollen was most viable and the stigmas were most receptive on the first day of flowering. The nectar had the maximum sugar content. The sexual reproduction system was mainly outcrossing, with some self-compatibility and a need for pollinators. After artificial self-pollination, fluorescent microscopy revealed the winding of pollen tubes. The predominant flower-visiting insects were Apis mellifera, Megachile sp., Syrphus corollae, Episyrphus balteatus, and Lasioglossum sp., among which A. mellifera, Megachile sp., and Lasioglossum sp. were effective pollinators. Understanding the pollination mechanisms and strategies of I. setosa provides basic reference data on the potential for reproduction, and conservation efforts.